ANALISIS UNSUR – UNSUR PROSA DALAM NOVEL AYAH KARYA ANDREA HIRATA - Mila Nirmala Sari Hasibuan (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Every human being can work one of them can be poured in the form of a novel, which contains the outpouring of a human heart that can be tangible experiences, ideas, feelings, enthusiasm or beliefs of the author or writer which is poured in a form of a description of the life of Literature in three parts: (1) prose, (2) poetry, (3) drama, novels included in the prose section. The novel is included in the category of new prose, has a complex interwoven story, such as Andrea Hirata's work on Father's novel, the focus of the research problem is analyzing the parts of Andrea Hirata's prose in Father's novel. This research aims to describe the parts of Andrea Hirata's prose in the novel Father, with a qualitative research design while the data collection technique is done through library techniques and document analysis is done by reading the data according to the theory used, data analysis techniques using hermeneutics techniques, the results of the study show that the prose parts of Andrea Hirata's work on Father novel are: Themes: Love, Rejection, Affection, Loyalty and Friendship. The plot used is a mixture of characters from Sabari, Zorro, Marlena, Ukur and Tamat, the Belitong story set in parts of Sumatra and Australia with a time frame from the 1980s to 2013, using a third-person perspective in the style of personification language disclosure, metaphor, hyperbole and using the Malay-Belitong diction.